1998
DOI: 10.1007/s002770050365
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma in younger patients: the role of age as prognostic factor

Abstract: The presenting features of 356 previously untreated multiple myeloma (MM) patients grouped according to age were analyzed in order (a) to elucidate the possible differences in initial clinical and laboratory features between patients younger than 50 years and the older ones and (b) to statistically assess the prognostic value of the parameters considered, with particular emphasis on the prognostic impact of age. Patients were divided into two groups: group I included 61 patients aged less than 50, group II com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 32 publications
1
29
0
3
Order By: Relevance
“…Another relevant finding of this study is the low proportion of young patients observed in the entire group of patients studied, a phenomenon that had been addressed in some prior studies. 3,4,14 In our investigation, 16% of the patients were younger than 50 years, 3% were younger than 40 years, and 0.26% were younger than 30 years.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Another relevant finding of this study is the low proportion of young patients observed in the entire group of patients studied, a phenomenon that had been addressed in some prior studies. 3,4,14 In our investigation, 16% of the patients were younger than 50 years, 3% were younger than 40 years, and 0.26% were younger than 30 years.…”
Section: Discussionmentioning
confidence: 47%
“…A previous study in 61 patients aged younger than 50 years showed no difference in presenting features compared with older patients. 3 Survival was significantly better compared with the older patient cohort but was significantly shorter in young patients after findings were corrected for differences in life expectancy. 3 Blade et al reported an increased frequency of renal impairment (30%) and hypercalcemia (29%) at presentation and median survival of 54 months in 72 patients younger than 40 years.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Younger patients present with more favorable features and have a better survival. Factors associated with improved survival include young males with low International Staging System (ISS) and Durie-Salmon stage, good performance status, and absence of poor prognostic features as high CRP, low hemoglobin, and severe renal insufficiency [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…La plupart d'entre eux ont plus de 50 ans, tandis que 10-15 % sont dans la quarantaine ou moins (Corso, 1998). Avec la chimiothérapie conventionnelle, la durée médiane de survie est de 3 ans.…”
Section: Abrégéunclassified